THE EFFECTIVENESS AND SAFETY OF BEDAQUILINE-CONTAINING REGIMENS IN THE TREATMENT OF PATIENTS WITH MULTI-DRUG RESISTANT TUBERCULOSIS (MDR-TB): A SYSTEMATIC LITERATURE REVIEW - Miptah Farid Thariqulhaq; Tri Yunis Miko Wahyono (Jurnal EduHealth, 2023)
Objective: MDR-TB is a life-threatening infectious disease. In recent years, RR/MDR TB sufferers have increased by 10% from 186,883 patients in 2018 to 206,030 in 2019. The success rate of treatment for RR/MDR-TB patients only reaches 57% globally. WHO has recommended bedaquiline for treatment of MDR-TB as the first drug in an all-oral regimen designed to maximize treatment outcomes. Purpose: to describe the efficacy and safety of a bedaquiline-containing regimen for the treatment of MDR-TB. Methods: Pubmed, Science Direct, and Embase online databases were used to obtain data published in the last five years where literature searches were carried out independently by researchers. The keywords used in this search are combined with the Boolean operator "AND", namely (bedaquiline) AND (multidrug resistant) AND (effectiveness). Results: Eight studies met the inclusion criteria, demonstrating a higher conversion rate of sputum cultures on the bedaquiline containing regimen between 74%-95.8% with a mean time to culture conversion between 39 days-3 months. The majority of studies reported an adverse effect of QT prolongation in patients treated with bedaquiline. Conclusion: This systematic review showed that bedaquiline is effective and safe for use in the treatment of MDR-TB. However, serious side effects of QT prolongation occurred in some respondents who were treated with bedaquiline, so an effective and efficient monitoring and surveillance system is needed to ensure best practice in the treatment of MDR-TB.